Hemorrhagic fever with renal syndrome in a child early age - D. O. Ivanov; V. N. Timchenko; E. B. Pavlova; N. V. Pavlova; A. N. Nazarova; T. M. Chernova; N. D. Savenkova; M. O. Revnova; I. I. Grafskaya; T. V. Yakovleva; O. V. Bulina (Журнал инфектологии)
In Russia, Hemorrhagic Fever with Renal Syndrome (HFRS) takes the leading place among all natural focal infections, the incidence rate in 2018 was 3,99 per 100 thousand population. In the Northwestern Federal District of the Russian Federation, HFRS occurs much less frequently – 1,46 cases per 100 thousand population. The disease is more susceptible to men aged 16–50 years, children rarely get sick. In 2019, 73 cases of HFRS (1,36 per 100 thousand population) were registered in St. Petersburg, among them only 2 episodes – in children under 18 years of age. A clinical case of HFRS in a child aged 1 year and 8 months is presented. The diagnosis was established on the basis of clinical and epidemiological data (acute onset of the disease, the presence of fever, thrombohemorrhagic syndrome, oliguria, anuria, information on cases of HFRS at the place of residence of the child) and laboratory data (detection of specific IgM antibodies to the Hantaan virus) in the later stages of the disease. The described case should alert pediatricians regarding possible natural focal diseases, including HFRS. A thorough analysis of the anamnestic, epidemiological and clinical data of the patient will help in the early stages of the disease to suggest a diagnosis, conduct laboratory diagnostics and prescribe appropriate therapy.